2016
DOI: 10.1371/journal.pone.0153723
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Amino Acids 471-507 of Avian Hepatitis E Virus Capsid Protein Are Crucial for Binding to Avian and Human Cells

Abstract: The infection of chickens with avian Hepatitis E virus (avian HEV) can be asymptomatic or induces clinical signs characterized by increased mortality and decreased egg production in adult birds. Due to the lack of an efficient cell culture system for avian HEV, the interaction between virus and host cells is still barely understood. In this study, four truncated avian HEV capsid proteins (ORF2-1 – ORF2-4) with an identical 338aa deletion at the N-terminus and gradual deletions from 0, 42, 99 and 136aa at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition to viral replication, virus attachment to host cells is considered to be another crucial step in viral infections (Schneider-Schaulies, 2000; Yugo et al, 2016). It is reported that the capsid protein region from amino acid 471 to 507 is critical for avian HEV attachment to host cells (Zhang et al, 2016) and the C-terminal region of the capsid ORF2 protein is recognized as putative binding sites for both cellular receptors and neutralizing antibodies (Ahmad et al, 2011). Wang et al (2018) utilized Lactococcuslactis as a delivery vector expressing higher levels of ΔORF2 (avian HEV truncated ORF2 protein spanning amino acids 249–606 protein) specific IgG antibodies, in order to neutralize or bind to avian HEV and induce effective mucosal immunity, prevented the virus from invading into host cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition to viral replication, virus attachment to host cells is considered to be another crucial step in viral infections (Schneider-Schaulies, 2000; Yugo et al, 2016). It is reported that the capsid protein region from amino acid 471 to 507 is critical for avian HEV attachment to host cells (Zhang et al, 2016) and the C-terminal region of the capsid ORF2 protein is recognized as putative binding sites for both cellular receptors and neutralizing antibodies (Ahmad et al, 2011). Wang et al (2018) utilized Lactococcuslactis as a delivery vector expressing higher levels of ΔORF2 (avian HEV truncated ORF2 protein spanning amino acids 249–606 protein) specific IgG antibodies, in order to neutralize or bind to avian HEV and induce effective mucosal immunity, prevented the virus from invading into host cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…ap237 attachment to different cell lines. In a previous study, it was documented that ap237 can imitate natural avian HEV particles and attach to LMH cells (30). In this study, the variations of ap237 attachment to differently treated LMH cell lines expressing different levels of OATP1A2 were first analyzed.…”
Section: Primermentioning
confidence: 99%
“…This region corresponded with the amino acid region of the human HEV p239 protein. In some previous studies, the results showed that ap237 contains most of the antigenic epitopes of avian HEV (18)(19)(20) and the key domain (aa 471 to 507) for binding to LMH cells (30) derived from chicken hepatocellular carcinoma epithelial cells (31), which support avian HEV replication (32). Next, ap237 was employed as a bait protein to target the host factors in chicken liver tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis of the full or nearly complete genome of aHEV strains identified four different genotypes and showed a distant relationship to mammalian and swine HEVs (50 to 60% nucleotide sequence identity) (Smith et al, 2015). The aHEV genotype 1 has been described in Australia and Korea, genotype 2 in USA, genotype 3 in Europe and China, and more recently, genotype 4 in Hungary and Taiwan (Payne et al, 1999;Park et al, 2015;Wang et al, 2015;Moon et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 98%